2023
DOI: 10.3389/fnut.2023.1127188
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum selenium concentration is associated with lower risk of all-cause and cardiovascular mortality among individuals with chronic kidney disease: A population-based cohort study of NHANES

Abstract: BackgroundSelenium is an essential nutrient and trace element required for human health and plays an important role in antioxidative and anti-inflammatory processes. However, the long-term impact of selenium levels on the health of patients with chronic kidney disease remains unclear.MethodParticipants in this study were 3,063 CKD adults from the Third National Health and Nutrition Examination Survey (NHANES 1999–2000, 2003–2004, and 2011–2018). The mortality status and the cause of death of the study particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…58 A population-based cohort study conducted using NHANES data concluded that individuals with higher selenium intake had significantly lower odds of having a high vascular risk status compared with those with lower selenium intake. 59 The crucial role of vitamin C in the autonomic nervous regulation of blood pressure has also been highlighted in a review, 60 emphasising its significance. It has been proposed that vitamin C restores baroreflex dysfunction induced by oxidative stress, mitigating baroreflex sensitivity and sustaining a hypertensive state.…”
Section: Discussionmentioning
confidence: 99%
“…58 A population-based cohort study conducted using NHANES data concluded that individuals with higher selenium intake had significantly lower odds of having a high vascular risk status compared with those with lower selenium intake. 59 The crucial role of vitamin C in the autonomic nervous regulation of blood pressure has also been highlighted in a review, 60 emphasising its significance. It has been proposed that vitamin C restores baroreflex dysfunction induced by oxidative stress, mitigating baroreflex sensitivity and sustaining a hypertensive state.…”
Section: Discussionmentioning
confidence: 99%